2021
DOI: 10.1371/journal.ppat.1009879
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza A virus susceptibility, infection, transmission, and antibody kinetics in European starlings

Abstract: Avian influenza A viruses (IAVs) pose risks to public, agricultural, and wildlife health. Bridge hosts are spillover hosts that share habitat with both maintenance hosts (e.g., mallards) and target hosts (e.g., poultry). We conducted a comprehensive assessment of European starlings (Sturnus vulgaris), a common visitor to both urban and agricultural environments, to assess whether this species might act as a potential maintenance or bridge host for IAVs. First, we experimentally inoculated starlings with a wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…However, a positive signal was not detected in the three cloacal samples collected from the same H5N6-infected group. This result corroborated the lower viral load of cloacal samples compared to fecal samples reported for AIVs [ 53 , 54 ], as this trend was observed for the H5N6 and H9N2 viruses included in the present study. We also observed more mucus in cloacal than in fecal samples, and thus our system should be further optimized to detect viruses in cloacal samples.…”
Section: Discussionsupporting
confidence: 92%
“…However, a positive signal was not detected in the three cloacal samples collected from the same H5N6-infected group. This result corroborated the lower viral load of cloacal samples compared to fecal samples reported for AIVs [ 53 , 54 ], as this trend was observed for the H5N6 and H9N2 viruses included in the present study. We also observed more mucus in cloacal than in fecal samples, and thus our system should be further optimized to detect viruses in cloacal samples.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we assessed the general premise that the risk of IAV transmission to poultry may be associated with flock size was evaluated for European starlings. A recent publication indicated that indirect transmission of IAV to starlings from water contaminated by IAV‐infected mallards is possible if not highly probable (Ellis et al., 2021). If large numbers of starlings become infected by drinking from and bathing in a small waterbody previously contaminated with virus by waterfowl, these same starlings could, in turn, travel to one or more livestock facilities where they could then environmentally transmit an IAV by depositing virus within feeders or waterers in facilities that do not exclude them.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the shared water sources in our animal rooms were likely the key vehicle from which quail were exposed to IAV in the current study. Notably, a recent study provided evidence that starlings become infected with IAVs following their exposure to relatively small water bodies used by IAV‐infected mallards ( Anas platyrhynchos ) (Ellis et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations